2014
DOI: 10.1002/term.1886
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring a cytoactive factor in a wound bed promotes healing

Abstract: Wound healing is a complex process that requires the intervention of cytoactive factors. The one-time application of soluble factors to a wound bed does not maintain a steady, sufficient concentration. Here we investigate the benefits of anchoring a factor in a wound bed via a tether to endogenous collagen. We use a collagen mimetic peptide (CMP) as a pylon. The CMP binds to damaged but not intact collagen and thus localizes a pendant cytoactive factor in the regions of a wound bed that require intervention. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…Our work, as well as other works with CMPs, have demonstrated that the incorporation of multiple CMPs onto a nanostructure/polymers dramatically affects mobility in collagen-based scaffolds due to the affinity CMPs have, particularly for remodeled collagen [73]. The reversible, serum-stable reaction prevents CMP-modified materials from leaving the delivery site[48], and as demonstrated here, can be used to both control and localize release. Other matrix-mediated gene delivery approaches have achieved similar expression periods as achieved in this work ranging from days[74, 75] to a month[76] within similar subcutaneous animal implants, while some have achieved multi-month expression periods [58].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our work, as well as other works with CMPs, have demonstrated that the incorporation of multiple CMPs onto a nanostructure/polymers dramatically affects mobility in collagen-based scaffolds due to the affinity CMPs have, particularly for remodeled collagen [73]. The reversible, serum-stable reaction prevents CMP-modified materials from leaving the delivery site[48], and as demonstrated here, can be used to both control and localize release. Other matrix-mediated gene delivery approaches have achieved similar expression periods as achieved in this work ranging from days[74, 75] to a month[76] within similar subcutaneous animal implants, while some have achieved multi-month expression periods [58].…”
Section: Discussionmentioning
confidence: 65%
“…Animal models have demonstrated that CMPs can be used to detect areas of excessive remodeling, such as tumors and joints [47], and CMPs can anchor cytoactive factors and collagen in wound beds to improve wound closure and granulation [48]. Utilizing a mouse model, in vivo gene expression in polyplex encapsulating or GPP-PEI polyplex-modified subcutaneous Matrigel® pellets was monitored.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been used to promote wound healing in mice. 164 The administration of exogenous cytoactive factors by subcutaneous or intraperitoneal injection or by topical application is compromised by natural lavation that rapidly dilutes and ultimately drains soluble molecules. In contrast, the one-time application of a collagen mimetic peptide–Substance P conjugate enhances wound healing compared to unconjugated Substance P and other controls, and does so with extensive re-epithelialization and mitigated inflammatory activity.…”
Section: Collagen Mimetic Peptidesmentioning
confidence: 99%
“…protein). Conjugating imaging agents can turn this peptide into diagnostic imaging agents, and attaching drug molecules can turn it into targeted drug delivery system [108110]. …”
Section: Targeting and Monitoring Denatured Collagen (Dn-collagen)mentioning
confidence: 99%
“…Therapeutic application of CHP was demonstrated by Raines and coworkers where (PPG) 7 was conjugated to substance P (SubP), a neuropeptide involved in wound healing [110]. Similar to peptides based on GPO sequence, the (PPG) 7 can hybridize with damaged collagen molecules at the wound site, allowing the SubP which is conjugated (PPG) 7 to be anchored in the wound bed and prevent scar tissue formation.…”
Section: Targeting and Monitoring Denatured Collagen (Dn-collagen)mentioning
confidence: 99%